Strategi Media Sosial BEM Universitas Padjadjaran Dalam Memberikan Informasi Dan Advokasi Kepada Mahasiswa - Azka Surya Putra Ardiansyah; Engkus Kuswarno; Ira Mirawati (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2024)
This study investigates Padjadjaran Care's Social Media Strategy within the Padjadjaran University Student Executive Board (BEM Kema Unpad). This research uses a qualitative descriptive case study approach and drawing from media ecology and media dependency theories. The research also examines social media selection, content planning, interaction strategies, and management evaluation. Data collection involved structured and semi-structured in-depth interviews with Padjadjaran Care social media managers from 2019 to 2023 and long-term followers. Findings reveal key aspects warranting further exploration: the selection of social media platforms (Line and Instagram) influenced by the evolving audience characteristics; content planning focused on addressing student needs via Instagram's question boxes; a commitment to 24-hour responsiveness in interactions, offering informative content; and an evaluation process through a mid-year review uploaded on BEM Kema Unpad's Instagram, capturing aspirations conveyed via Instagram direct messages and Line Official Account chat.